PENERAPAN HERBISIDA ORGANIK EKSTRAK ALANG-ALANG UNTUK MENGENDALIKAN GULMA PADA MENTIMUN - Gayuh Prasetyo Budi; Oetami Dwi Hajoeningtijas (Universitas Muhammadiyah Purwokerto, 2013)
This research was conducted to study the application of thatch grass extract to weed control, to study the growth and yield of cucumber. The experiment was carried out from January 2013 to April 2013 and was conducted in Dukuhwaluh village, Kembaran District in Banyumas Regency. The research was arranged in a Complete Randomized Design with 1 factor and 5 replications. The factor was application concentration of thatch grass extract consisted of: without application, 100 g/l, 200 g/l, 300 g/l and clean weeding. The results showed that the application concentration of thatch grass extract (200 g/l) can reduce weed population in cucumber crops. Concentration’s application of thatch grass extract (200 g/l) effective to increase fruit number/plant and fruit weight/plant of cucumber. Key words: thatch grass extract, weed populatio and cucumber.